2021
DOI: 10.1371/journal.pone.0246201
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and livestock adaptations to demographic growth and technological change: A diachronic perspective from the Late Bronze Age to Late Antiquity in NE Iberia

Abstract: There are strong interactions between an economic system and its ecological context. In this sense, livestock have been an integral part of human economies since the Neolithic, contributing significantly to the creation and maintenance of agricultural anthropized landscapes. For this reason, in the frame of the ERC-StG project ’ZooMWest’ we collected and analyzed thousands of zooarchaeological data from NE Iberia. By considering these data in comparison with ecological indicators (archaeobotanical remains) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
0
11
0
9
Order By: Relevance
“…Sheep and goat bones are also known to vary in size diachronically (e.g. Davis, 2008;Espinet et al, 2021;Grau-Sologestoa, 2015). From the results provided by the analysis of 143 modern specimens from 13 different breeds, we conclude that the lower third molar size has a low discriminatory power and, as such, it has a…”
Section: Sheep/goat Differencesmentioning
confidence: 86%
“…Sheep and goat bones are also known to vary in size diachronically (e.g. Davis, 2008;Espinet et al, 2021;Grau-Sologestoa, 2015). From the results provided by the analysis of 143 modern specimens from 13 different breeds, we conclude that the lower third molar size has a low discriminatory power and, as such, it has a…”
Section: Sheep/goat Differencesmentioning
confidence: 86%
“…In recent years, the study of settlement and production patterns of Iron Age communities in northeastern Iberia (4th−3rd century BCE), described as "Iberians" in ancient literary sources, has increased our knowledge of the exploitation of their natural resources and the development of proto-urban societies. Studies of their diversified agricultural production, patterns of grinding and storage (Alonso and Pérez-Jordà, 2019), and livestock strategies (Colominas et al, 2020;Nieto-Espinet et al, 2021;Messana et al, 2023a,b) have identified an intensive exploitation of agro-pastoral resources. The development of urban communities has also been highlighted, suggesting that their largest sites (oppida) acted as the capitals of polities corresponding to some of the ethnic territories mentioned in the ancient written sources (civitates; Sanmartí et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sheep (Ovis aries) and goat (Capra hircus) are two important species of agro-pastoral systems in the Mediterranean basin since the Neolithic and were often herded together [21][22][23][24][25][26][27][28][29]. However, they possess distinct ecological [30,31] and economical properties [32][33][34][35][36], making it of prime interest to establish secure identifications of ancient specimens before studying the two species separately.…”
Section: Introductionmentioning
confidence: 99%